Applying the WHO recommendations on health-sector response to violence against women to assess the Spanish health system. A mixed methods approach - Isabel Goicolea; Carmen Vives-Cases; Fauhn Minvielle; Erica Briones-Vozmediano; Ann Öhman (Elsevier, 2014)
This methodological note describes the development and application of a mixed-methods protocol to assess the responsiveness of Spanish health systems to violence against women in Spain, based on the World Health Organization (WHO) recommendations. Five areas for exploration were identified based on the WHO recommendations: policy environment, protocols, training, accountability/monitoring, and prevention/promotion. Two data collection instruments were developed to assess the situation of 17 Spanish regional health systems (RHS) with respect to these areas: 1) a set of indicators to guide a systematic review of secondary sources, and 2) an interview guide to be used with 26 key informants at the regional and national levels. We found differences between RHSs in the five areas assessed. The progress of RHSs on the WHO recommendations was notable at the level of policies, moderate in terms of health service delivery, and very limited in terms of preventive actions. Using a mixed-methods approach was useful for triangulation and complementarity during instrument design, data collection and interpretation.